Eddy covariance fluxes over a boreal Scots pine forest - Markkanen, T.; Rannik, U.; Keronen, P.; Suni, T.; Vesala, T. (Boreal Environment Research Publishing Board, 2024)
We report the results on eddy covariance measurements of net ecosystem exchange (NEE) and accompanying latent and sensible heat fluxes for 44 months in boreal Scots pine forest (southern Finland). We analysed the temperature dependence of ecosystem respiration and PPFD (photosynthetic photon flux density) dependence of daytime CO2 exchange and calculated the annual carbon budget filling the gaps in data series with the temperature and light dependences. The estimated annual balances of the NEE's were –234 g C m–2, –262 g C m–2 and –191 g C m–2 in 1997, 1998 and 1999, respectively. We calculated also NEE's for every possible 365-day periods included in the data series and the maximum and minimum of such NEE's were –165 g C m–2 and –304 g C m–2. The growing season started around 28 April, 16 April and 25 March in 1997, 1998 and 1999, respectively. The maximum light saturated CO2 uptake rate reached the value of 12 umol m–2 s–1 gradually by the end of June. In autumn, the uptake did not decline gradually but ceased rapidly round the beginning of November. The non-growing season activity is also important, because soil carbon decomposition occurs all year around, even in cold climates under snow cover. The wintertime average CO2 respiration rate was 0.44 umol m–2 s–1.